Balancing Governance Capacity and Legitimacy: How the Norwegian Government Handled the COVID‐19 Crisis as a High Performer. (16th July 2020) - Christensen, Tom; Lægreid, Per
Abstract: This essay addresses how the Norwegian government has handled the coronavirus pandemic. Compared with many other countries, Norway has performed well in handling the crisis. This must be understood in the context of competent politicians, a high‐trust society with a reliable and professional bureaucracy, a strong state, a good economic situation, a big welfare state, and low population density. The Norwegian government managed to control the pandemic rather quickly by adopting a suppression strategy, followed by a control strategy, based on a collaborative and pragmatic decision‐making style, successful communication with the public, a lot of resources, and a high level of citizen trust in government. The alleged success of the Norwegian case is about the relationship between crisis management capacity and legitimacy. Crisis management is most successful when it is able to combine democratic legitimacy with government capacity.